Structural characterizarion of extensive farms in Andalusian dehesas - García, A.; Perea, J.; Acero, R.; Angón, E. (Arch. Zoot, 2010)
Three types of livestock farming systems are identified in Andalusian dehesas using multivariate analysis. One of two conservationist systems, both applying sustainable management criteria, was detected in most of farms: dehesa farming system (49% of farms): small extensive cattle and sheep farms, which adapt stocking rates to the availability of the land's natural resources, and occasional use of strategic food supplementation; mountain farming system (21%) also relative to small farms, with mainly small ruminants and limited use of technology. The third system was a yield targeted system (30%), corresponding mainly to large cattle farms, with greater use of technology and high levels of food supplementation caused by stocking rates that exceed the land's carrying capacity. Typology defined can be used as starting point to base technical and economic characterization of farming systems taking into consideration their current and future viability
Keywords: Factorial analysis; Farm typology; Livestock farming systems

Producción de bellota en la dehesa: factores influyentes - Rodríguez-Estévez, V.; García, A.; Perea, J.; Mata, C.; Gómez, A. G. (Arch. Zootec, 2007)
This paper reviews the state-of-the- knowledge of acorn production in the South- Western Iberian dehesas. In the first part are briefly described the soil and climatic determining factors and phenology of most common trees of genus Quercus at the dehesa (Q. ilex, Q. suber and Q. faginea). In the second part, acorn production estimations are analyzed. Was established a mean acorn yield of 300 to 700 kg/ ha; with individual productions of 8-14 kg/tree for Q. ilex, 5-10 kg/tree for Q. suber and 1-11 kg/ tree for Q. faginea; with a highly variable production, both between and within years and individual trees. Finally we review the factors affecting acorn production, describing density of trees (estimated in 20-50 trees/ha), masting phenomenon (with cycles of 2-5,5 years and asynchrony between trees), individual cha- racteristics of trees (genetic potential, age, top surface, etc.), tree mass handling (with favourable effect of tilling, moderate pruning and sustainable grazing), meteorological conditions (mainly drought and meteorology during flowering) and sanitary status (Lymantria, Tortrix, Curculio, Cydia, Balaninus and Brenneria).
Keywords: Agro forestry system; evergreen oak; iberian pig; Mast-seeding; Montanera; Quercus